2019
DOI: 10.1016/j.socscimed.2019.112545
|View full text |Cite
|
Sign up to set email alerts
|

Using community health workers to deliver a scalable integrated parenting program in rural China: A cluster-randomized controlled trial

Abstract: Inadequate care during early childhood can lead to long-term deficits in skill development. Parenting programs are promising tools for improving parenting practices and opportunities for healthy development. We implemented a non-masked cluster-randomized controlled trial in rural China in order to assess the effectiveness of an integrated home-visitation program that includes both psychosocial stimulation and health promotion at fostering development and health outcomes of infants and toddlers in rural China. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 46 publications
2
41
0
5
Order By: Relevance
“…As found by a growing body of literature, a child’s early development could bring high returns to his/her welfare in adulthood [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ] and the long-term economic growth of the country [ 9 ]. The key findings of this paper strongly indicated that delivering the information on positive parenting practices to the caregiver is indeed beneficial to the child’s ECD outcomes, which is in line with the findings of Sylvia et al [ 21 ] and Luo et al [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As found by a growing body of literature, a child’s early development could bring high returns to his/her welfare in adulthood [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ] and the long-term economic growth of the country [ 9 ]. The key findings of this paper strongly indicated that delivering the information on positive parenting practices to the caregiver is indeed beneficial to the child’s ECD outcomes, which is in line with the findings of Sylvia et al [ 21 ] and Luo et al [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, in rural China, many caregivers never receive the information to help them to create a stimulating home environment, so they do not know how to successfully stimulate their children’s development [ 15 , 20 ]. Furthermore, some parenting programs that delivered parenting information to caregivers in rural areas found that, in the intervention group, family care in terms of parental investments increased by 0.35–0.72 standard deviation (SD), and the child’s cognitive development increased by 0.23–0.27 SD [ 21 , 22 ]. These findings indicated that family care might mediate in the links between parenting information and child development.…”
Section: Introductionmentioning
confidence: 99%
“…In some provinces of China, such as Shaanxi [42], Hebei, and Yunnan Provinces [43], several parenting intervention programs have been initiated to improve early child development of rural children. These programs have seen an increase in children's development outcomes by 0.23-0.27 SD in treatment households.…”
Section: Discussionmentioning
confidence: 99%
“…In some areas of rural China, such as Shaanxi Province [36], Yunnan and Hebei Province [37], some parenting intervention programs have been conducted to improve the child's development outcomes. The findings in this paper indicate that the improvement in a caregiver's parenting skills may be one important channel between parenting intervention and early childhood development.…”
Section: Discussionmentioning
confidence: 99%